Study of Mitotic Activity and Chromosomal Behaviour in Root Meristem of Allium cepa L. Treated with Magnesium Sulphate - Bhatta, Prabhakar; Sakya, S. R. (Ecoprint: An International Journal of Ecology, 2009)
The mitotic activity and chromosomal behaviour was observed in four different concentrations of magnesium sulphate at four different duration of treatment using Allium cepa as a biological system. Mito-inhibitory effect of the compound was observed in higher concentration. The compound was capable of producing various chromosomal abnormalities indicating the cytostatic and clastogenic properties of magnesium sulphate. Key words: Allium cepa, magnesium sulphate, mitotic index, phase indices. doi: 10.3126/eco.v15i0.1947 ECOPRINT 15: 83-88, 2008